MODERASI BERAGAMA BERBASIS KEARIFAN LOKAL MASYARAKAT HINDU TRANSMIGRAN DI KECAMATAN LANDONO SULAWESI TENGGARA - Putu Diantika; Ayu Indah Cahyani (Jurnal Pendidikan Agama, 2023)
Moderation is not a rigid, passive, static attitude. Moderation is an attitude that is not excessive in dealing with the problems of difference in a pluralistic society. Moderate attitude is active and dynamic with noble ideals, namely social change in a positive, fair, and balanced direction. Practicing religious teachings needs to consider the principles of moderation and local wisdom as an effort to avoid deviations from religious teachings. This study aims to describe the religious moderation attitude of the Hindu community in the transmigrant area based on local wisdom in Landono District, Southeast Sulawesi Province. This study uses a qualitative descriptive approach with observation and interview techniques and literature study. The results of this study indicate that the attitude of religious moderation based on local wisdom is implemented by transmigrant Hindus in the Landono sub-district of Southeast Sulawesi where even though they are far from the island of Bali and become immigrant communities and become communities with minority religions in the province, they can live side by side peacefully with practice the teachings of Susila, Tat Twam Asi and Tri Hita Karana with the concept of menyama braya, namely respecting differences and placing others as family. The attitude of religious moderation can have positive implications for the transmigrant Hindu community in forming religious awareness in carrying out the teachings of Hinduism as a way to build a harmonious life